How Does The Changes in Monetary Policy Affect Lending Behavior of Islamic Banking in Malaysia - Fathin Faizah Said; Abd Ghafar Ismail (Universitas Islam Indonesia, 2007)
This paper tries to analyse the role of Islamic banks in the transmission of monetary policy and business cycle. This study will only analyse the Islamic banking in Malaysia. The changes in the monetary policy channel give an idea to regulate and strengthen the banking industry. Thus, several questions can be highlighted: how do the changes in the monetary policy tools affect the bank lending? If bank lending plays as monetary policy channel, do they affect the other portfolio? Do the current regulations (such as capital requirement) af-fect the Islamic bank lending? Furthermore, Generalize Least Squares approach will be us-ing to estimate the monetary changes towards Islamic banks portfolio. Annual data will be used from the year 1997 until 2004. The number of observations is based on the combination of time series and cross-sectional data, which is known as pooled data. Instead of that, we will use an unbalanced bank-level panel data set for Islamic banks (i.e., two full-pledged Islamic banks and thirteen Islamic windows).JEL Classification numbers: E51, E52, E58Keywords: Transmission Mechanism; Monetary Policy; Lending Channel